Analysis of Factors Affecting the Performance of Medical Laboratory Technologists (MITS)/Laboratory Analysts in Hospitals: A Scoping Review - Agus Riyanto; Ayun Sriyatmi; Cahya Tri PurnamiI (Eduvest - Journal of Universal Studies, 2026)
The performance of Medical Laboratory Technologists (MLTs) and Laboratory Analysts is essential for maintaining the accuracy and reliability of diagnostic services in hospitals. Suboptimal laboratory performance can negatively affect clinical decision-making and patient outcomes. Many hospitals in Indonesia face challenges such as limited staffing, high workloads, and inadequate career development systems, which may hinder optimal employee performance. This study aims to systematically analyze key factors influencing the performance of Medical Laboratory Technologists and Laboratory Analysts in hospital settings. A systematic review methodology was applied by synthesizing findings from multiple related studies to derive comprehensive conclusions. Literature searches were conducted using Google Scholar and focused on factors associated with employee performance, including compensation, leadership, motivation, work culture, organizational commitment, work environment, salary structures, and career development, with article selection restricted to publications from 2014 to 2024. Articles were screened through title and abstract review, followed by full-text assessment based on eligibility criteria. The review results indicate that compensation, leadership, motivation, and work culture are major determinants of performance, while organizational commitment, work environment, salary structures, and career development also significantly contribute to job satisfaction and productivity. The findings highlight that strengthening both financial and non-financial incentives, providing effective leadership, and fostering supportive organizational cultures can enhance employee performance and improve the efficiency and quality of laboratory services.